Neglected tropical diseases: an effective global response to local poverty-related disease priorities - Dirk Engels; Xiao-Nong Zhou (BMC, 2020)
Abstract Background Neglected tropical diseases (NTDs) have long been overlooked in the global health agenda. They are intimately related to poverty, cause important local burdens of disease, but individually do not represent global priorities. Yet, NTDs were estimated to affect close to 2 billion people at the turn of the millennium, with a collective burden equivalent to HIV/AIDS, tuberculosis, or malaria. A global response was therefore warranted. Main text The World Health Organization (WHO) conceived an innovative strategy in the early 2000s to combat NTDs as a group of diseases, based on a combination of five public health interventions. Access to essential NTD medicines has hugely improved thanks to strong public-private partnership involving the pharmaceutical sector. The combination of a WHO NTD roadmap with clear targets to be achieved by 2020 and game-changing partner commitments endorsed in the London Declaration on Neglected Tropical Diseases, have led to unprecedented progress in the implementation of large-scale preventive treatment, case management and care of NTDs. The coming decade will see as challenges the mainstreaming of these NTD interventions into Universal Health Coverage and the coordination with other sectors to get to the roots of poverty and scale up transmission-breaking interventions. Chinese expertise with the elimination of multiple NTDs, together with poverty reduction and intersectoral action piloted by municipalities and local governments, can serve as a model for the latter. The international community will also need to keep a specific focus on NTDs in order to further steer this global response, manage the scaling up and sustainment of NTD interventions globally, and develop novel products and implementation strategies for NTDs that are still lagging behind. Conclusions The year 2020 will be crucial for the future of the global response to NTDs. Progress against the 2020 roadmap targets will be assessed, a new 2021-2030 NTD roadmap will be launched, and the London Declaration commitments will need to be renewed. It is hoped that during the coming decade the global response will be able to further build on today's successes, align with the new global health and development frameworks, but also keep focused attention on NTDs and mobilize enough resources to see the effort effectively through to 2030.